Selective Priming of Tumor Blood Vessels by Radiation Therapy Enhances Nanodrug Delivery - Kunjachan, Sijumon; Kotb, Shady; Pola, Robert; Pechar, Michal; Kumar, Rajiv; Singh, Bijay; Gremse, Felix; Taleeli, Reza; Trichard, Florian; Motto-Ros, Vincent; Sancey, Lucie; Detappe, Alexandre; et al. (Scientific reports, 2019)
Effective drug delivery is restricted by pathophysiological barriers in solid tumors. In human pancreatic adenocarcinoma, poorly-permeable blood vessels limit the intratumoral permeation and penetration of chemo or nanotherapeutic drugs. New and clinically viable strategies are urgently sought to breach the neoplastic barriers that prevent effective drug delivery. Here, we present an original idea to boost drug delivery by selectively knocking down the tumor vascular barrier in a human pancreatic cancer model. Clinical radiation activates the tumor endothelial-targeted gold nanoparticles to induce a physical vascular damage due to the high photoelectric interactions. Active modulation of these tumor neovessels lead to distinct changes in tumor vascular permeability. Noninvasive MRI and fluorescence studies, using a short-circulating nanocarrier with MR-sensitive gadolinium and a long-circulating nanocarrier with fluorescence-sensitive nearinfrared dye, demonstrate more than two-fold increase in nanodrug delivery, post tumor vascular modulation. Functional changes in altered tumor blood vessels and its downstream parameters, particularly, changes in Ktrans (permeability), Kep (flux rate), and Ve (extracellular interstitial volume), reflect changes that relate to augmented drug delivery. The proposed dual-targeted therapy effectively invades the tumor vascular barrier and improve nanodrug delivery in a human pancreatic tumor model and it may also be applied to other nonresectable, intransigent tumors that barely respond to standard drug therapies.
Keywords: patologická angiogeneze; endoteliální buňky pupečníkové žíly (lidské); Gold; Cell Line, Tumor; optické zobrazování; magnetická rezonanční angiografie; Neoplasms, Experimental; zlato; Magnetic Resonance Angiography; Human Umbilical Vein Endothelial Cells; kovové nanočástice; Drug Delivery Systems; Animals; Metal Nanoparticles; lidé; experimentální nádory; Humans; Optical Imaging; zvířata; Neovascularization, Pathologic; myši; nádorové buněčné linie; Mice; lékové transportní systémy